Badania zagęszczalności kruszyw używanych w budownictwie drogowym = Research of density of aggregate materials used in road building - Ćwiąkała, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of this article is to show how quality and durability of a road is dependant upon the correct density of its? ground base, which lies under the surface of the paving. A well prepared base should guarantee the load capacity and, where needed, isolate the road from the unfavourable ground conditions. Curve diagrams in this article show how to determine the optimal moisture and density of the ground framework.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); wilgotność optymalna; gęstość objętościowa szkieletu gruntowego; badanie w aparacie Proctora; zagęszczanie gruntów; optimal moisture; ground framework density; Proctor's apparatus test; ground density